A Novel Strength Model for Cement Marine Clay Based on the Mechanical-Chemical Coupling Behavior - Xu, Liyang; Yan, Zihai; Yan, Jiajia; Xu, Qiliang; Zhu, Jiancai; Xu, Riqing (Journal of marine science and engineering, 2021)
Crucial mechanical-chemical (MC) interactions occur during the cement hydration process in cement marine clay; however, the role of such an important element of the resulting strength has been subject to less investigation, particularly from the theoretical perspective. To overcome this scientific gap, an efficient strength-based model accounting for the coupled MC processes is proposed here. Based on the analysis of the cement hydration mechanism, the porosity was chosen as the main factor to characterize the influence of the MC interactions on the overall response. To verify the accuracy of the MC model, the unconfined compressive strength (UCS) experiment was conducted for the cement marine clay samples, and the corresponding simulation model was constructed using COMSOL multiphysics®. In addition, a comparison between the predicted results by the existing three strength models and the proposed MC model was performed. Subsequently, the sensitivity analysis and identification of mechanical parameters were carefully carried out. The obtained results show that the UCS strength for Taizhou clay ranges from 10.21 kPa to 354.2 kPa as the cement content increases from 10% to 20%, and the curing time varies from 3 days to 28 days. The mechanical parameters in the MC model can be obtained according to the porosity level. A reasonably good agreement between the UCS strength results of simulations and the experimentally observed data is reported. Additionally, the predicted UCS strength results by the MC model demonstrate the best correspondence with the measured values, indicating the high efficacy of the established model.